2016
DOI: 10.1111/jan.13201
|View full text |Cite
|
Sign up to set email alerts
|

Associations of changes in psychosocial factors and their interactions with diabetes distress in patients with type 2 diabetes: a longitudinal study

Abstract: Nurses could endeavour to improve the diabetes self-efficacy and resilience to reducing diabetes distress. Arbitrarily empowering patients may increase diabetes distress. Increasing self-care management behaviours and patient empowerment might need to be simultaneously addressed to reduce the diabetes distress in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 35 publications
3
35
1
3
Order By: Relevance
“…In agreement to a study among Taiwanese patients (8-item PAID) [40] but in contrast to non-Asian patients [4], we found higher DD levels in people who reported more days of self-care activities. This association could be bidirectional.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement to a study among Taiwanese patients (8-item PAID) [40] but in contrast to non-Asian patients [4], we found higher DD levels in people who reported more days of self-care activities. This association could be bidirectional.…”
Section: Discussionsupporting
confidence: 91%
“…This study determined that baseline social support directly affected baseline diabetes distress, which is consistent with longitudinal studies that determined baseline social support affected subsequent diabetes distress (Karlsen & Bru, ; Wang et al., ). Social support can help people cope with stressful events (Baek et al., ).…”
Section: Discussionsupporting
confidence: 85%
“…This study was a 1‐year longitudinal study and a follow‐up of a cross‐sectional study (Lee, Lee, & Moon, ). Part of the results related to this research has been reported in previous publications (Wang et al., , ). In this study, data at three time points for six monthly intervals were collected to test the hypothesized model.…”
Section: Methodssupporting
confidence: 57%
“…Diabetes‐related self‐care activities are activities that include taking care of oneself, maintaining health and controlling the progression of diabetes (Wang et al, ). The recommended DRSCA for people with T2DM generally include healthy eating, medication, physical activity, blood glucose self‐monitoring and foot care (Toobert, Hampson, & Glasgow, ).…”
Section: Introductionmentioning
confidence: 99%
“…The recommended DRSCA for people with T2DM generally include healthy eating, medication, physical activity, blood glucose self‐monitoring and foot care (Toobert, Hampson, & Glasgow, ). To prevent complications, people with T2DM have to manage DRSCA daily (Wang et al, ). However, based on a systematic review, the performance of DRSCA among people with T2DM was not optimal in China (Luo et al, ) and in many other countries (Blackburn, Swidrovich, & Lemstra, ).…”
Section: Introductionmentioning
confidence: 99%